Statistical techniques for the study of language and language behaviour - Rietveld, Toni; Hout, Roeland van (Mouton de Gruyter, 1993)
A textbook on statistical techniques covering an unusually wide range of techniques and subjects, from classic techniques like analysis of variance and multiple regression to reliability and agreement analysis, matrix algebra, factor analysis, log linear modeling, and logistic regression. The emphasis is less on mathematical aspects than on how sta